Hydraulic Performance Modifications of a Zeolite Membrane after an Alkaline Treatment: Contribution of Polar and Apolar Surface Tension Components. (19th February 2015) - Dutournié, Patrick; Said, Ali; Daou, T. Jean; Bikaï, Jacques; Limousy, Lionel
Abstract : Hydraulic permeability measurements are performed on low cut-off Na-mordenite (MOR-type zeolites) membranes after a mild alkaline treatment. A decrease of the hydraulic permeability is systematically observed. Contact angle measurements are carried out (with three polar liquids) on Na-mordenite films seeded onto alumina plates (flat membranes). A decrease of the contact angles is observed after the alkaline treatment for the three liquids. According to the theory of Lifshitz-van der Waals interactions in condensated state, surface modifications are investigated and a variation of the polar component of the material surface tension is observed. After the alkaline treatment, the electron-donor contribution (mainly due to the two remaining lone electron pairs of the oxygen atoms present in the zeolite extra frameworks) decreases and an increase of the electron-receptor contribution is observed and quantified. The contribution of the polar component to the surface tension is attributed to the presence of surface defaults, which increase the surface hydrophilicity. The estimated modifications of the surface interaction energy between the solvent (water) and the Na-mordenite active layer are in good agreement with the decrease of the hydraulic permeability observed after a mild alkaline treatment.